2017
DOI: 10.22159/ijpps.2017v9i10.20935
|View full text |Cite
|
Sign up to set email alerts
|

Production and Characterization of Exopolysaccharide From Marine Moderately Halophilic Bacterium Halomonas Smyrnensis SVD Iii

Abstract: Objective: To study 1) Optimization of nutritional and environmental parameters to enhance the yield of EPS by Halomonas smyrnensis SVD III isolated from seawater, West Coast of Maharashtra, India and 2) Purification and characterization of the EPS produced. Methods:The isolate was grown in Sehgal and Gibbons (SG) medium broth supplemented with 3% glucose, at 37 °C, 120 rpm for 7 d. Optimization of different parameters was carried out with one factor at a time approach. EPS was isolated from cell-free supernat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 40 publications
(46 reference statements)
0
11
0
Order By: Relevance
“…While carbon and nitrogen sources and the concentrations of salts had significant effects on the production of polymers in Yangia , the amount of EPS produced so far (60–70 mg/g CDW) was low compared with that reported for other halophiles such as Halomonas alkaliantarctica, Halomonas eurihalina , Halomonas maura, Halomonas xianhensis , H. smyrnensis, and Hfx. mediterranei (Biswas & Paul, 2017a,b; Deshmukh et al, 2017; Sarilmiser et al, 2015; Cui et al, 2017b), but in the same range as that for Halomonas ventosae (Mata et al, 2006). Further studies are needed to determine the conditions for increasing the production of EPS, its characteristics, and its potential applications.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…While carbon and nitrogen sources and the concentrations of salts had significant effects on the production of polymers in Yangia , the amount of EPS produced so far (60–70 mg/g CDW) was low compared with that reported for other halophiles such as Halomonas alkaliantarctica, Halomonas eurihalina , Halomonas maura, Halomonas xianhensis , H. smyrnensis, and Hfx. mediterranei (Biswas & Paul, 2017a,b; Deshmukh et al, 2017; Sarilmiser et al, 2015; Cui et al, 2017b), but in the same range as that for Halomonas ventosae (Mata et al, 2006). Further studies are needed to determine the conditions for increasing the production of EPS, its characteristics, and its potential applications.…”
Section: Discussionmentioning
confidence: 98%
“…No absorption peaks around the region of 1700–1770 cm −1 attributed to C=O stretching of carbonyls in esters were observed (Kielak et al, 2017). The peak in the region of 1644 cm −1 would represent the absorption band of carboxylic groups, suggesting the presence of acidic sugars (Deshmukh et al, 2017; Kielak et al, 2017), and similarly, the peak at 1219 cm −1 observed in some samples could be attributed to C‐O stretching in ether or alcohol groups (Gu et al, 2017; Kanamarlapudi & Muddada, 2017). The peak at 1051 cm −1 indicates a possible α (1→6) glucosidic bond with certain flexibility (Gu et al, 2017), while the absorption band at 978 cm −1 suggests the vibrations of the glycosidic bonds C‐O‐C and the peak in the region of 840–860 cm ‐1 are characteristic of α‐D‐glucan (Kanamarlapudi & Muddada, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In certain scenarios, the nutritional conditions can also influence the molecular weight and the EPS osidic composition. It has been shown that a novel Alteromonas macleodii strain produces 23.4 g/ L exo polysaccharide when grown on 15% of lactose, the highest yield for marine EPS [24,25,26,27,28,29] .…”
Section: Introductionmentioning
confidence: 99%